Controlled‐rate freezing to regulate the structure of collagen–glycosaminoglycan scaffolds in engineered skin substitutes. Issue 4 (18th August 2014) - Lloyd, Christopher; Besse, John; Boyce, Steven
Abstract: Controlled‐rate freezing (CRF) of biopolymer scaffolds may increase reproducibility of microstructure compared with analog processes. Freezing of collagen–glycosaminoglycan (CG) scaffolds by CRF with liquid nitrogen at chamber cooling rates of −80, −40, −20, or −10°C/min, was compared with submersion in 95% ethanol at −55°C. Cooling rates of −80 or −40°C/min generated scaffolds with pore areas and pore fractions that were comparable to scaffolds frozen in ethanol. Test and control scaffolds were populated with human dermal fibroblasts and epidermal keratinocytes to generate engineered skin substitutes (ESS) and evaluated for surface hydration and mitochondrial metabolism. ESS with scaffolds frozen by CRF at −80 or −40°C/min were comparable with, or better than, ESS with control scaffolds ( p < 0.05). These results demonstrate that fabrication of CG scaffolds by CRF offers advantages of digital programming, as well as greater reproducibility, safety, and simplicity than submersion in chilled ethanol without compromise of biological properties required for biomedical applications. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 832–840, 2015.